The organisational capacity for social innovation: an experiential exploration in re-ordering institutional practices - Petousis, Francois George (Research of GSB, 2017)
This study is an exploratory attempt to develop theoretical insights into the organisational capacity for social innovation, utilising a qualitative inquiry into the internal and external practices of a socially focussed organisation. By appreciating the lived experiences of engaging in these practices, the research looks to surface elements that contribute to the social sensitivity required to engage the complexity of social systems. Based in the social constructivism of Berger & Luckman (1966), and the associated institutional theory, seeing the structures which "enable and constrain agents" (Cajaiba-santana, 2014), the research contributes to the fields of collaborative experiential surfacing (W. Nilsson & Paddock, 2013) and resilience within social innovation (Westley, 2013). Through an autoethnographic data collection process, the findings of this study come to witness the different elements of how experiential practises can bring to an organisation a deep connection to social nuances, and challenge traditional structures of authority. The emerging nature of the social innovations developed and the dialogical relationships that support this, are found to be key elements in the context of this study.